The Desirable Health Indicator: A New Indicator of Population Health and Healthcare Utilisation - Doel, Harri; Griffiths , Lucy J; Johnson, Rhodri David; Turner, Samantha; Lyons , Ronan A; Lyons , Jane (International Journal of Population Data Science, 2026)
Background and Objective Healthcare research faces challenges in developing metrics that resonate with the general public or policymakers. We created a Desirable Health Indicator (DHI) to address this gap, centred around New Year's wishes for survival and non-occurrence of undesired events in the following year, for the population of Wales, UK, following discussions with policymakers and members of the public. Methods We created retrospective, population-based individual-level cohorts from linked routinely collected anonymised, health and demographic data from the Secure Anonymised Information Linkage (SAIL) Databank (2015-2022). The DHI was calculated per person per year and quantified the distribution of the population who survive calendar years and do not use selected health services (not admitted to hospital; no emergency department attendance; and not prescribed medication used in infection, analgesics, or mental health drugs). Group and individual interviews were held with members of the public and policy makers seeking their views of the indicator. Results The findings were understood and well received by members of the general public and policymakers. Between 2015 and 2019, the percentage of individuals meeting the DHI ranged between 39.6%-41.9%, increasing to 48.6% and 46.2% for2020 and 2021respectively, and reducing to 43.1% in 2022. Focussing on the year 2022, 1,154,630 (43.1%) met the DHI from a population of 2,677,829. The percentage of people with desirable health decreased significantly with age and with increasing socioeconomic deprivation. A higher proportion of males (49.2%) met the DHI compared to females (37.1%). Being male (aOR = 1.62 [95%CI 1.61,1.63]), 10-19 years of age (aOR = 1.69 [95%CI 1.68,1.71]), and living in the least deprived areas of Wales (aOR = 1.31 [95%CI 1.30,1.32]) were the characteristics associated with the highest odds of meeting the desirable health indicator. The most prevalent reasons for not meeting the indicator were GP prescriptions for drugs used in infections (29.5%), analgesics (22.8%) and mental health conditions (20.2%). Conclusion The DHI provides an insightful and novel tool for monitoring aspects of population health and healthcare utilisation. The DHI's coverage of important topics, derived from routine data sources, makes it a reproducible, temporally flexible, and easily understood indicator, suitable for informing policy development and addressing aspects of health inequalities. As data linkage capabilities expand internationally there are opportunities for implementation to aid comparison and better understanding of how systems perform.